Alive failures behind the windows of cancer therapy - Islam, Muhammad (International Journal of Medicine, 2017)
The multiscope process, cancer is attributable from various geneses. Eventually, cancer is a complicated disease with unconstrained interca-lation and impacts on the physiological system. Therefore, an ideal cancer therapy must be like a multi-edged sword. Broadly, currently, available cancer therapies are the cytoprotective, inhibitors of oncogenes, correctors, and cell destructors. Doubtless, cancer therapists are most frequently handling apoptosis and autophagy inducers, targeting of tumor suppressor genes, epigenetic and immune therapies. How-ever, each therapy has a number of challenges yet to be resolved. This revision is aimed to find out some important points, depicting till the date, how successful we are and what are the failures behind those modes of therapeutic strategies.